Validation of IPM strategy in Bt cotton in whitefly (Bemisia tabaci) hot spot of North-West India - KUMAR, ANOOP; BIRAH, AJANTA; TANWAR, R K; KHOKHAR, M K; SINGH, S P; MONGA, D; KUMAR, RISHI; ARORA, J K (The Indian Journal of Agricultural Sciences, 2021)
Bt cotton has witnessed the increasing infestation of sucking pests especially whitefly during last one decade. During 2015, whitefly (Bemisia tabaci Ishii) emerged as a serious pest in North India destroyed 2/3 of the cotton crop in Punjab. There was an urgent need to validate integrated pest management (IPM) strategy for management of whitefly in Bt cotton in hot spot area with farmer's participatory mode. To overcome the problem, ICAR-NCIPM initiated a trial on validation of IPM in cotton at Fazilka, Punjab in 2.5 ha during 2016, which was extended to 12 ha and 40 ha area in the year 2017 and 2018 respectively. The validated IPM strategy included timely sowing of recommended cotton hybrid, removal of weed as alternate host, proper plant nutrition along with foliar spray of 2% potassium nitrate, use of neem based pesticides, conservation of natural enemies by avoidance of insecticides which are harmful to natural enemies, and judicious use of safer pesticides. IPM implementation resulted in successful management of whitefly and other pests with significant increase in population of natural enemies predators along with significant reduction in the number of insecticides spray (>68%) and amount of active ingredients (>84%) in IPM fields as compared to FP (Farmer's practice) fields. IPM implementation also brought > 18% increase in yield, > 17% reduction in input cost and >90% increase in net profit compared to FP. The benefit-cost ratio in IPM was 2.55 against 1.88 in FP.